Removal and recovery of heavy metals from sewage sludge via three-stage integrated process - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ; YEŞİL, HATİCE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Heavy metal contamination of sewage sludge is one of the concerns preventing its land application. Traditional processes applied for stabilization of sewage sludge are still inadequate to serve sustainable solutions to heavy metal problem. In this study, fermentation and bioleaching potentials of sewage sludge were investigated in anaerobic reactors for either non-pretreated or ultrasonicated sludge at three different pH regimes (free of pH regulation, acidic, and alkaline). The results of the study revealed that combination of ultrasonication pretreatment and alkaline fermentation performed the best among the other cases, resulting in 33.7% hydrolysis, 10.5% acidification, 11-33% metal leaching, and up to 25% reduction in bioavailability of potentially toxic heavy metals. Bioleaching effluent obtained from the best performing reactor was subjected to membrane-based metal recovery. A supported liquid membrane impregnated with a basic carrier successfully recovered soluble metals from the bioleaching effluent with an efficiency of 39-68%. This study reveals that the proposed three-stage process, ultrasonication pretreatment-alkaline fermentation-supported liquid membrane, effectively produces stable sludge with reduced heavy metal toxicity and recovers metals from organic waste streams. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Anaerobic fermentation; Bioleaching; Pretreatment; Ultrasonication; Volatile fatty acids; Waste activated sludge; WASTE ACTIVATED-SLUDGE; FATTY-ACIDS ACCUMULATION; ANAEROBIC-DIGESTION; FULL-SCALE; HYDROLYSIS; SEPARATION; SOLVENT; FRACTIONATION; FERMENTATION; PRETREATMENT